Degradation of methyl orange by ozone in the presence of ferrous and persulfate ions in a rotating packed bed. (March 2016) - Ge, Deming; Zeng, Zequan; Arowo, Moses; Zou, Haikui; Chen, Jianfeng; Shao, Lei
Abstract: This work investigated the degradation of methyl orange by ozone in the presence of ferrous and persulfate ions ( O 3 / Fe 2 + / S 2 O 8 2 − ) in a rotating packed bed. The effects of various operating parameters such as initial pH, rotational speed, gas–liquid ratio, ozone inlet concentration and reaction temperature on the degradation rate of methyl orange were studied with an aim to optimize the operation conditions. Results reveal that the degradation rate increased with an increase in rotational speed, gas–liquid ratio and ozone inlet concentration, and reached a maximum at 25 °C and initial pH 4. Contrast experiments involving ozone and ferrous ions (O3 /Fe 2+ ) were also carried out, and the results show approximately 10% higher degradation rate and COD removal in the O 3 / Fe 2 + / S 2 O 8 2 − process than in the O3 /Fe 2+ process. Additionally, the intermediates of the degradation process were analyzed to ascertain the degradation products. Highlights: Methyl orange was treated by the ferrous-catalyzed sodium persulfate and ozone (O3 /Fe 2+ /PS) process. A rotating packed bed was used to intensify the O3 /Fe 2+ /PS process. The O3 /Fe 2+ /PS process showed better degradation effect than the O3 /Fe 2+ process. The intermediates of methyl orange degradation were identified.